2018
DOI: 10.1089/ars.2017.7346
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reactive Oxygen Species and Type 1 Diabetes

Abstract: Mechanistic studies are needed to investigate the mitochondrial pathways involved in autoimmunity, including T1D. These studies should seek to identify the role of mitochondria in regulating innate and adaptive immune cell activity and beta cell failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 105 publications
2
66
0
Order By: Relevance
“…Alternatively, hydroxylation of the alpha subunit of HIF1α is inhibited by increased succinate/fumarate levels that occur when flux through the tricarboxylic acid (TCA) cycle slows, referred to as pseudohypoxia [30]. Mitochondrial dysfunction is an early manifestation of autoimmunity directed at beta cells and, therefore, the most likely inducer of activation of HIF1α signalling in type 1 diabetes [31]. The decreased density and perinuclear distribution of mitochondria noted in beta cells in type 1 diabetes in the current study resembles that observed as a defensive adaptation to stress accomplished by metabolic remodelling to high glycolysis and decreased oxidative phosphorylation [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, hydroxylation of the alpha subunit of HIF1α is inhibited by increased succinate/fumarate levels that occur when flux through the tricarboxylic acid (TCA) cycle slows, referred to as pseudohypoxia [30]. Mitochondrial dysfunction is an early manifestation of autoimmunity directed at beta cells and, therefore, the most likely inducer of activation of HIF1α signalling in type 1 diabetes [31]. The decreased density and perinuclear distribution of mitochondria noted in beta cells in type 1 diabetes in the current study resembles that observed as a defensive adaptation to stress accomplished by metabolic remodelling to high glycolysis and decreased oxidative phosphorylation [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In HG conditions and/or fatty acid oxidation, therefore, ROS overproduction causes cellular dysfunction, apoptosis, and inflammation in several insulin targets including the pancreas, liver, kidney, nerves, and vasculature [17,18].…”
Section: Pathophysiology Of Diabetes-related Metabolic Disorders Andmentioning
confidence: 99%
“…For instance, in T1DM, the generated ROS under metabolic or autoimmune stress in the cells of the pancreatic microenvironment may enhance damage of pancreatic β-cells, thereby reducing insulin secretion [17]. Regarding T2DM, HG-induced ROS production is considered a major contributor to damage and disease progression.…”
Section: Pathophysiology Of Diabetes-related Metabolic Disorders Andmentioning
confidence: 99%
“…Recent work demonstrating mitochondrial metabolic defects linked to inflammatory responses in immune cells of T1D donors may suggest an unexplored role for CLEC16A-mediated mitophagy in T1D(7,56). Likewise, defective mitophagy has been associated with elevated secretion of cytokines by macrophages(57,58).…”
mentioning
confidence: 99%